Asymmetrical Chirality in 3D Bended Metasurface. (29th April 2021) - Pan, Ruhao; Liu, Zhe; Zhu, Wei; Du, Shuo; Gu, Changzhi; Li, Junjie
Abstract: Chiral metasurfaces offer crucial opportunities to expand the application potential for chiral photonics, but its desired freely structural control and giant circular dichroism (CD) allow for more and greater challenges. Here, different from previous metasurfaces with single structural regulation, a kind of bifunctional chiral metasurface based on 3D bended asymmetric construction is proposed, which shows giant CD combined with asymmetric chirality at 5.2 µm. The bended metasurface with abundant spatial freedom, consisting of an array of asymmetric bended split ring resonators (SRRs), can be built up from the tensile stress induced by focused ion beam (FIB)–matter interaction. The results show that the CD increases with the bending angle of the metasurface and reaches a maximum at a bending angle of 60°. Particularly, it is found that the CD is 0.71/0.85 (experiment/simulation) for the backward incidence but −0.29/−0.29 for the forward incidence, indicating that the giant CD and asymmetric chirality properties are realized simultaneously in the same metasurface. The calculated results of near‐field distribution and the electric/magnetic dipoles show that the giant CD and the asymmetric chirality come from p → ⋅ m → ≠ 0 and | p → × m → | ≠ 0, respectively. The findings inspire a high efficiency approach to design multifunctional chiral optical devices. Abstract : A 3D bended metasurface that works in the mid‐infrared range is designed and assembled by focused ion beam defined origami, showing an asymmetric circular dichroism (CD) property based on the different near field distributions under the opposite direction of light incidence. A small CD of 0.29 and giant CD of 0.71 is achieved for forward incidence and backward incidence, respectively.